Resolving molecule-specific information in dynamic lipid membrane processes with multi-resonant infrared metasurfaces - Daniel Rodrigo (Nature Portfolio, 2018)
Complex protein-lipid interactions are difficult to study in real-time without labels. Here, Rodrigo et al. introduce a multimodal plasmonic infrared biosensor to simultaneously distinguish multiple analytes with high sensitivity.